Indonesian Relations with the Eastern Europe, Soviet Union and China before 1965: Systemic and Domestic Factors - Mohd Noor Mat Yazid (2016)
This article discusses the Indonesian relations with Eastern Europe Communist states, Soviet Union and China Communists before 1965 and how the systemic and domestic factors influenced Indonesian decision. Indonesian foreign relation was closer to communist state after President Sukarno’s official visits to Moscow and Beijing in 1956. Why President Sukarno foreign relations closer to communist states? What was the international political situation that influenced Sukarno to lean to East bloc? What was the domestic situation that influenced Sukarno to do so? Why Indonesian closer relation with the communist not began earlier than 1956? Among the main discussions in this article are: the Indonesian-Soviet Union relations, Indonesian-China relations, Communist ideology and Indonesian relations with Eastern European Communists states. Indonesian relations with Communists state changed dramatically after the Indonesian Coup of September 1965 and the collapsed of President Sukarno and the formation of “new order” regime under Suharto in Indonesia. The changes of domestic politics in Indonesia after September 1965 strongly influenced the Indonesian relations with the Communists states.